“Christmas star”’ by Boris Pasternak and Iosif Brodsky: conventional ekphrasis as the interpretation of a gospel plot - Автухович, Татьяна (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper examines the interpretation of the gospel plot about Christ’s birth and the adoration of the Magi in the poems of Boris Pasternak and Iosif Brodsky. The poets emphasize the philosophical potential of the plot and reveal various personal meanings in it, which is conditioned by the passage of time and the changing historical contexts. While Pasternak focuses on the embedding of the Christmas plot in the national and the world culture, Brodsky problematizes the theme.